The lignicolous fungus Trametes versicolor (L.) Lloyd (1920): a promising natural source of antiradical and AChE inhibitory agents - Ljiljana Janjušević; Maja Karaman; Filip Šibul; Giuseppina Tommonaro; Carmine Iodice; Dragica Jakovljević; Boris Pejin (Taylor & Francis Group, 2017)
This study aimed to determine antiradical (DPPH• and •OH) and acetylcholinesterase (AChE) inhibitory activities along with chemical composition of autochtonous fungal species Trametes versicolor (Serbia). A total of 38 phenolic compounds with notable presence of phenolic acids were identified using HPLC/MS-MS. Its water extract exhibited the highest antiradical activity against •OH (3.21 μg/mL), among the rest due to the presence of gallic, p-coumaric and caffeic acids. At the concentration of 100 μg/mL, the same extract displayed a profound AChE inhibitory activity (60.53%) in liquid, compared to donepezil (89.05%), a drug in clinical practice used as positive control. The flavonoids baicalein and quercetin may be responsible compounds for the AChE inhibitory activity observed. These findings have demonstrated considerable potential of T. versicolor water extract as a natural source of antioxidant(s) and/or AChE inhibitor(s) to be eventually used as drug-like compounds or food supplements in the treatment of Alzheimer's disease.